Advanced heart failure: guideline‐directed medical therapy, diuretics, inotropes, and palliative care - Daniela Tomasoni; Julie K.K. Vishram‐Nielsen; Matteo Pagnesi; Marianna Adamo; Carlo Mario Lombardi; Finn Gustafsson; Marco Metra (ESC Heart Failure)
Abstract Heart failure (HF) is a major cause of mortality, hospitalizations, and reduced quality of life and a major burden for the healthcare system. The number of patients that progress to an advanced stage of HF is growing. Only a limited proportion of these patients can undergo heart transplantation or mechanical circulatory support. The purpose of this review is to summarize medical management of patients with advanced HF. First, evidence‐based oral treatment must be implemented although it is often not tolerated. New therapeutic options may soon become possible for these patients. The second goal is to lessen the symptomatic burden through both decongestion and haemodynamic improvement. Some new treatments acting on cardiac function may fulfil both these needs. Inotropic agents acting through an increase in intracellular calcium have often increased risk of death. However, in the recent Global Approach to Lowering Adverse Cardiac Outcomes Through Improving Contractility in Heart Failure (GALACTIC‐HF) trial, omecamtiv mecarbil was safe and effective in the reduction of the primary outcome of cardiovascular death or HF event compared with placebo (hazard ratio, 0.92; 95% confidence interval, 0.86–0.99; P = 0.03) and its effects were larger in those patients with more severe left ventricular dysfunction. Patients with severe HF who received omecamtiv mecarbil experienced a significant treatment benefit, whereas patients without severe HF did not (P = 0.005 for interaction). Lastly, clinicians should take care of the end of life with an appropriate multidisciplinary approach. Medical treatment of advanced HF therefore remains a major challenge and a wide open area for further research.